(untitled) (Environment & Health, 2026)
The aim. The purpose of the study is to assess the risk of exposure to electric and magnetic fields for the health of the population of. Zaporizhzhia, which lives within the sanitary protection zone of high-voltage power lines of industrial frequency with a capacity of 150-330 kW. Materials and methods. The work was carried out taking into account the requirements and recommendations of the International Commission for Protection against Non-ionizing Radiation. 832 measurements of electromagnetic radiation were carried out using the PZ-50 industrial frequency field strength meter, which was calibrated. Measurements were carried out on the basis of Standard operating procedure «Methodology for measuring the level of electromagnetic radiation in the territory of residential buildings, in the premises of residential, public and industrial buildings». Research results. 27 monitoring points were identified, where the indicators of the electric field strength did not exceed the maximum permissible limits and the potential risk for the population was assessed as acceptable. However, at 4 points, the indicators of the electric field were registered at the limit of normal and the level of potential risk was estimated as permissible, and at one point, in which the excess of the maximum permissible level was determined, the potential risk for the population was estimated as extremely high (dangerous). Conclusions. 1. The results of the study made it possible to assess the potential risk of health of the population of. Zaporizhzhia from the influence of electromagnetic fields of high-voltage power lines of industrial frequency with a capacity of 150-330 kW. 2. As a result of the study, a monitoring point was identified, where an excess of the maximum permissible level and, accordingly, a high (dangerous) level of potential risk were observed. 3. Information about the results of the work was sent to the authorities and network owners for their further management decisions.